Design of a hybrid wind/solar energy converter for integration into utility grid - Lu, Yirun (2019)
Wind and solar energy are two sources of energy that are readily available in everyday life. The two elements are experienced by people on a daily basis; in the daily commute to school, doing outdoor activities, have an alfresco dining. With such abundance, it would be a waste not to tap on these resources to reduce the use of traditional non-renewable energy. A hybrid wind and solar energy converter can be the answer to a more sustainable form of energy production compared to traditional energy sources. The two sources of energy must first be able to be captured by their respective method; Solar via the use of solar panels, and wind via wind turbines. In order to integrate these two sources of energy into our daily life, it must then be able to integrate into the utility grid seamlessly. In this project simulation, both energy sources will be captured by their respective circuits, combined to a common circuit, then converted to integrate with the utility grid.